Occult prostate carcinoma with metastasis to the mandible presenting as numb chin syndrome - Upasana Sethi Ahuja; Devi Charan Shetty; Akshay Rathore; Manu Dhillon (Elsevier, 2021)
Prostate cancer is one of the leading causes of death due to malignancy in men. Occult malignancy presenting with no primary symptoms could be a challenge to the diagnostician. Metastasis of prostate carcinoma to the mandible is rare and usually presents with non-specific symptoms. Only 1% of oral cancers account for lesions which present as metastasis of other primary malignancies. We report a rare case of prostate carcinoma being diagnosed as metastasis to the mandible with the patient presenting with numb chin syndrome.